Chitosan derivatives targeting lipid bilayers: Synthesis, biological activity and interaction with model membranes - Martins, Danubia Batista; Nasário, Fábio Domingues; Silva-Gonçalves, Laiz Costa; de Oliveira Tiera, Vera Aparecida; Arcisio-Miranda, Manoel; Tiera, Marcio José; dos Santos Cabrera, Marcia Perez (Elsevier, 2017)
The antimicrobial activity of chitosan and derivatives to human and plant pathogens represents a high-valued prospective market. Presently, two low molecular weight derivatives, endowed with hydrophobic and cationic character at different ratios were synthesized and characterized. They exhibit antimicrobial activity and increased performance in relation to the intermediate and starting compounds. However, just the derivative with higher cationic character showed cytotoxicity towards human cervical carcinoma cells. Considering cell membranes as targets, the mode of action was investigated through the interaction with model lipid vesicles mimicking bacterial, tumoral and erythrocyte membranes. Intense lytic activity and binding are demonstrated for both derivatives in anionic bilayers. The less charged compound exhibits slightly improved selectivity towards bacterial model membranes, suggesting that balancing its hydrophobic/hydrophilic character may improve efficiency. Observing the aggregation of vesicles, we hypothesize that the charge cluster mechanism, ascribed to some antimicrobial peptides, could be applied to these chitosan derivatives.
Keywords: Antimicrobial and tumoricidal activities; Charge cluster mechanism; Chitosan-lipid bilayer interaction; Hydrophobic/hydrophilic balance; Lytic activity; Quaternized chitosan